Measuring the Impact of Quality Improvement in a Software Company - Cătălin AFRĂSINEI (Revista de Management Comparat International)
The quality issue is not only a matter of developing and implementing a quality system. It mandatory this system to function precisely on a long term basis. The evaluation of quality impact as a consequence of its improvement is a scary thing the quality specialists prefer to be apart due to its complexity. That’s the reason why the article emphasize on: the need and justification of quality impact evaluation, particularities of quality in software domain generated by its specificity, what evaluation of economic effects means in the context of a quality improvement particularly in a software company, a proposed method to calculate the impact of quality (on the costs structure), a practical example of how the method should be used and the results interpreted based on two simulated case.